Job Creation Efforts through Empowering Micro, Small and Medium Enterprises - Rayhan Fahriza Yose (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Micro, small and medium enterprises or abbreviated UMKM are businesses established by individuals or business entities that provide economic services to the wider community that can overcome the economic crisis, are able to encourage Indonesia's economic growth by expanding employment opportunities. The method used in this Writing this journal is a normative legal research method that examines efforts to create jobs through empowering Micro, Small and Medium Enterprises. This legal research method is considered normative because researchers research by collecting data which is then analyzed qualitatively. Micro, Small and Medium Enterprises are the most important part of fulfilling the Indonesian economy which can reduce poverty and unemployment in the country. potential solutions to create jobs and drive economic growth. One way to empower MSMEs is to provide them with access to financial resources, technical assistance, and business development support. By providing MSMEs with access to financial resources such as microcredit and equity financing, they can expand their operations and increase production capacity, which can lead to the creation of new jobs.